Hubungan Derajat Luka dan Lama Menderita dengan Quality of Life pada Penderita Ulkus Diabetik di Klinik Ikram Wound Care Center Kabupaten Majene - Harli, Kurnia (Journal of Health Education and Literacy, 2020)
Abstract Diabetic ulcer is the most common complication of diabetes mellitus that had a detrimental effect on the patients’ physical and psychological state. These may impede patients' activity and productivity, therefore, it may reduce the quality of life of the patients. This study aimed to find out the relationship between the degree of the wound and the length of suffering to the quality of life in patients with diabetic ulcers at the Ikram wound care center Majene. The design of this study used a cross-sectional study design with a sample size of 36 respondents obtained by consecutive sampling methods, the data collections utilized the world health organization quality of life (WHOQOL) –BREF questionnaire and the degree of the wound and length of suffering observation sheet. The data were statistically analyzed using a chi-square test. The p-value of wound degree and quality of life was 0.251, this indicated that there was no relationship between the degree of the wound and the quality of life, furthermore, p-value of the length of suffering and quality of life was 1.000 which indicated that there was no relationship between the length of suffering and the quality of life.